Type 1 growth factor receptor expression in node positive breast cancer: adverse prognostic significance of c-erbB-4. Issue 4 (1st April 2003) - Lodge, A J; Anderson, J J; Gullick, W J; Haugk, B; Leonard, R C F; Angus, B
Abstract : Background: There is a clear need to define biological markers that will predict the response to treatment in breast cancer, and several recent studies suggest that the expression of type 1 growth factor receptors may prove important in this regard. The type 1 growth factor receptors are a family of transmembrane receptors comprising epidermal growth factor receptor (EGFR), c-erbB-2, c-erbB-3, and c-erbB-4. Both EGFR and c-erbB-2 are associated with poor prognosis in certain tumours. Aims: There is very little information concerning expression patterns of the full range of type 1 growth factor receptors, especially with respect to c-erbB-3 and c-erbB-4. Therefore, this study was designed to compare the expression of each, and to assess whether expression of any of the factors was related to patient survival in a clinical series. Methods: Type 1 growth factor receptor expression was investigated by means of immunohistochemistry in a series of node positive patients with breast cancer (n = 66), and statistical analysis was carried out to determine associations between variables and survival analysis for each variable. Results: There were several correlations between variables, and overexpression of EGFR, c-erbB-2, and c-erbB-4 was found to be associated with adverse clinical outcome, although the results were significant only for c-erbB-4 (p = 0.002). Conclusion: Although patient numbers are small, this is the first report describing c-erbB-4 as an adverse prognostic marker. These findings are in contrast to previous investigations and may relate to the fact that the patients studied all had advanced stage disease and had undergone similar chemotherapy regimens in the context of a clinical trial.